Aleukemic cutaneous myeloid sarcoma1. (8th October 2013) - Aboutalebi, Amir; Korman, John B.; Sohani, Aliyah R.; Hasserjian, Robert P.; Louissaint, Abner; Le, Long; Kraft, Stefan; Duncan, Lyn M.; Nazarian, Rosalynn M.
<x xml:space="preserve">Abstract</x> Background Aleukemic cutaneous myeloid sarcoma (CMS) represents an important yet rare entity denoting the presence of a cutaneous myeloid leukemic infiltrate without concurrent peripheral blood or bone marrow disease. The clinicopathologic diagnosis remains elusive due to isolated skin findings and variable immunostaining. Cytogenetic and molecular findings have infrequently been reported. Methods Twenty‐five patients with CMS were identified in the Massachusetts General Hospital pathology database between 2004 and 2012. Patients were excluded if concurrent blood or marrow acute myeloid leukemia (AML), myelodysplastic syndrome or lymphoproliferative disorder were diagnosed. Results Three patients were identified: a neonate with recurrent CMS and marrow disease that never met diagnostic criteria for AML and two patients relapsing as CMS without concurrent blood or marrow disease following chemotherapy‐induced complete remission. Histology showed atypical mononuclear cell interstitial dermal infiltrates. All cases were CD68+, lysozyme+ and CD117−; one of two were CD34+; two of three were myeloperoxidase negative. 11q23 rearrangement, t(1;14), NPM1 (nucleophosmin I), FLT3‐ITD (Fms‐like tyrosine kinase 3‐internal tandem duplication), and novel FLT3‐D835 mutations were identified. Conclusion An isolated atypical cutaneous infiltrate may represent aleukemic CMS and should prompt a search for other extramedullary sites of involvement. Immunohistochemistry, molecular and cytogenetic studies can help differentiate aleukemic CMS from benign and malignant, monocytic and histiocytic mimickers, and may potentially indicate therapy and prognosis.